Joint angle coordination strategies during whole body rotations on a single lower-imb support: An investigation through ballet pirouettes - Lott, M. B.; Xu, G. (Journal of Applied Biomechanics, 2020)
Despite the prevalence of turning maneuvers in everyday life, relatively little research has been conducted on joint angle kinematic coordination during whole-body rotations around a vertical axis. Ballet pirouettes provide an opportunity to study dynamically balanced, whole-body rotations on a single support and the potential to scale results to smaller angular displacements executed by general populations. The purpose of this study was to determine the supporting limb`s ankle, knee, hip, and pelvis-trunk joint angle excursions and kinematic coordination strategies utilized during the pirouette`s turn phase. Advanced dancers (n = 6) performed pirouettes while whole-body 3-dimensional kinematics were recorded. Group mean ankle ab/adduction excursion was significantly greater than all other excursions (P < .05). Principal components analysis was applied to joint angle time-series data (4 joints × 3 degrees of freedom = 12 variables). The first 4 principal components explained 92% (2%) of variance, confirming redundancy in joint angle data. Evolution of the data along the first principal component in successful pirouettes oscillated at the pirouette`s rotational frequency. Principal component eigenvector coefficients provided evidence of ankle-hip coordination, although specific coordination patterns varied between individuals and across trials. These results indicate that successful pirouettes are executed with continuous, oscillatory joint angle coordination patterns.